Adolescent’s knowledge about abortion - Hidayat, Anisa Apriarti Nur; Suherni, Suherni; Purnamaningrum, Yuliasti Eka (Poltekkes Kemenkes Yogyakarta, 2018)
Results of a reproductive health survey by Development Planning Agency at Sub-National Level  in Yogyakarta showed that teenage pregnancies that are caused by sexual intercourse reached 10,53% and all teenage pregnancies ended up in abortion. It is obvious that the knowledge that related to abortion is very important in preventing teenage deviant behaviour. The purpose of this study was done in order to found out level of knowledge about abortion towards the students of Bina Harapan Sleman Vacational Hihg School grade X in 2018. This research was a descriptive research with cross sectional design. This research was conducted on February - July 2018 The subjects were 65 students who were taken by total sampling technique. Measurement of knowledge level used questionnaire. Analysis of univariate data by calculating percentages. Results of this study is the level of knowledge about abortion in adolescents are  grade X in SMK Bina Harapan Sleman was mostly in sufficient category (48,4%). Mostly teenagers are male (75,8%), aged more than 15 years (71%) and got more information from school (35,5%). Male teenagers had better knowledge of female teenegers (8,5%), adolescents are aged more than 15 years had better knowledge (9,1%) and adolescents are got information from health workers (11,8%) and electronic media (20%) had better knowledge. The level of knowledge about adolescents are X grade in SMK Bina Harapan Sleman in sufficient category.